A Game-theoretic Framework to Identify Overlapping Communities in Social Networks - Chen, Wei; Liu, Zhenming; Sun, Xiaorui; Wang, Yajun (Data Mining and Knowledge Discovery Journal, special issue on ECML PKDD 2010, 21(2), September, 2010, pp. 224-240., 2010)
In this paper, we introduce a game-theoretic framework to address the community detection problem based on the structures of social networks. We formulate the dynamics of community formation as a strategic game called community formation game: Given an underlying social graph, we assume that each node is a selﬁsh agent who selects communities to join or leave based on her own utility measurement. A community structure can be interpreted as an equilibrium of this game. We formulate the agents’ utility by the combination of a gain function and a loss function. We allow each agents to select multiple communities, which naturally captures the concept of “overlapping communities”. We propose a gain function based on the modularity concept introduced by Newman (2006), and a simple loss function that reﬂects the intrinsic costs incurred when people join the communities. We conduct extensive experiments under this framework, and our results show that our algorithm is effective in identifying overlapping communities, and are often better then other algorithms we evaluated especially when many people belong to multiple communities. To the best of our knowledge, this is the ﬁrst time the community detection problem is addressed by a game-theoretic framework that considers community formation as the result of individual agents’ rational behaviors.